1988
DOI: 10.1159/000281427
|View full text |Cite
|
Sign up to set email alerts
|

New Results on the Pharmacokinetics of Fosfestrol

Abstract: For more than 30 years Fosfestrol (Honvan®) has been used as an estrogen for successful palliative therapy of prostatic carcinoma, but the pharmacokinetics of this compound were unknown due to the lack of analytical methods. Over the last few years we have developed a special extraction process for Fosfestrol and its metabolites from plasma with recovery yields > 90%. The simultaneous measurement of the most important compounds after intravenous and oral administration was achieved by high-performance liquid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 1 publication
3
12
0
Order By: Relevance
“…Previous studies showed that the enantiomers differ in their t 1/2 value considerably [12]. The present investigation analyzed cell biologic effects of chlormezanone racemate and (+)-and (-)-enantiomers in vitro.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies showed that the enantiomers differ in their t 1/2 value considerably [12]. The present investigation analyzed cell biologic effects of chlormezanone racemate and (+)-and (-)-enantiomers in vitro.…”
Section: Discussionmentioning
confidence: 92%
“…1). Other pharmacological and pharmacokinetic qualities are not specific for any of the enantiomers [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…4 From the point of view of thrombotic events, our series reiterates the experience of a number of studies, 5 and there is evidence that the intravenous route may even be safer than the oral route. 6 Pharmacokinetic studies 7 have demonstrated that peak plasma levels of fosfestrol are achieved very quickly, with rapid clearance of the principal metabolites. Pharmacokinetic pro®les seem not to be affected by daily repeated administration, nor by renal impairment, an important determinant given the ages of our patients and obvious tendencies towards renal impairment.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the reported fosfestrol assays are based on high performance liquid chromatography (HPLC) [4][5][6][7][8][9], batch [10,11] and automated spectrophotometry using flow injection analysis [12][13][14]. Capillary electrophoresis (CE) is a relatively "young" technique [15,16] gaining continuously growing attention and acceptance among scientists due to its unique features and advantages over traditional liquid chromatographic separation techniques.…”
Section: Introductionmentioning
confidence: 99%